Unravelling the Evolutionary Patterns and Ecological Significance of Bioluminescence in Deep-Sea Organisms - Ammnah Salim Qareerah; Hmaza Saad Massuod (African Journal of Advanced Pure and Applied Sciences, 2023)
Bioluminescence, a captivating natural phenomenon, manifests prolifically within the cryptic recesses of our deep oceans. This luminescent adaptation, not merely a spectacle, serves diverse ecological roles, from deceptive predation strategies to intricate communication modalities. Through advanced genomic and proteomic assessments, we unveil the multifarious evolutionary trajectories that have given rise to this luminosity in marine taxa. Concurrently, we probe the myriad ecological ramifications of bioluminescence, emphasizing its pivotal role in the survivalist tactics of deep-sea denizens. These light-emitting biochemical processes, predominantly encompassing the luciferin-luciferase catalytic reactions, have evolved in convergence across several marine lineages. The ecological implications of bioluminescence span predator-prey dynamics, reproductive signalling, and niche colonization. This paper endeavours to synthesize the current understanding of bioluminescence's evolutionary tapestry while spotlighting its significance as an ecological linchpin in the enigmatic deep-sea biosphere.